Public Services At The Samsat Office Of Brebes District (Study of Motorized Vehicle Taxpayers) - Simpati Nisa Wijaya; Siti Rodhiyah Dwi Istinah; Rakhmat Bowo Suharto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2020)
This study aims to determine the problems found in the Samsat Office regarding the maintenance of motor vehicle taxpayers.The method of approach used in this study uses the Sociological Juridical Approach Method, data using Descriptive specifications, data consisting of primary data and secondary data, analyzed with Quantitative, The data used are primary and secondary, primary data in the form of interviews, secondary data in the form of bibliography and laws. How to obtain data by interviewing and conducting research to SAMSAT Brebes Regency.Supporting factors and inhibiting factors Motor Vehicle Taxpayer Services have used the Online system that makes it easy for the public in the Extension of Motor Vehicle Taxpayer, Need to improve service excellence to the community regarding service obligation to pay vehicle tax and implement the SAMSAT program routinely, especially in places far from reach or in remote villages, this embodies the commitment to provide the best service for the communityKeywords : Public Services; Taxpayers; Motorized Vehicles.